A Complete Separation of Hexane Isomers by a Functionalized Flexible Metal Organic Framework. (21st October 2014) - Mendes, Patricia A. P.; Horcajada, Patricia; Rives, Sébastien; Ren, Hong; Rodrigues, Alírio E.; Devic, Thomas; Magnier, Emmanuel; Trens, Philippe; Jobic, Hervé; Ollivier, Jacques; Maurin, Guillaume; Serre, Christian; et al.
<x xml:space="preserve">Abstract</x> The separation ability of branched alkane isomers (nHEX, 3MP, 22DMB) of the flexible and functionalized microporous iron(III) dicarboxylate MIL‐53(Fe)‐(CF3)2 solid is evaluated through a combination of breakthrough experiments (binary or ternary mixtures), adsorption isotherms, X‐ray diffraction temperature analysis, quasi‐elastic neutron scattering measurements and molecular dynamics simulations. A kinetically controlled molecular sieve separation between the di‐branched isomer of hexane 22DMB from a mixture of paraffins is achieved. The reported total separation between mono‐ and di‐branched alkanes which was neither predicted nor observed so far in any class of porous solids is spectacular and paves the way towards a potential unprecedented upgrading of the RON of gasoline.